Use of Deixis Persona in Habiburrahman El Shirazy's Novel The Fading Charm of Cleopatra - Fariki Wahyudi; Asmiyati (Penerbit Hellow Pustaka, 2024)
This study aims to describe the use of deiksis persona in the novel The Fade of Cleopatra Charm by Habiburrahman El Shirazy. The method used in this study is qualitative descriptive with an analysis technique on the content of the novel text. The results of the study show that the types of persona deiksis used in the novel The Fading of Cleopatra's Charm include: (1) singular and plural first persona deiksis, (2) singular and plural second persona deiksis, and (3) singular and plural third persona deiksis. Each type of persona deiksis has a different function according to the context and reference. The first persona deiksis singularly is me and me, while the first persona deiksis is plural us and us. The singular second persona deiksis used is you and you, while the plural second persona deiksis is you. The third persona deiksis consists of the singular third persona deiksis, namely him and him, while the third persona deiksis is plural, namely them. The deiksis persona in this novel helps shape the dynamics of relationships between characters, provides emotional context, and enriches the narrative with diverse perspectives.